Profiling of the Transcriptomic Responses of Clonostachys rosea Upon Treatment With Fusarium graminearum Secretome - Demissie, Zerihun A.; Foote, Simon J.; Tan, Yifang; Loewen, Michele C. (Frontiers in Microbiology, 2018)
Clonostachys rosea strain ACM941 is a fungal bio-control agent patented against the causative agent of Fusarium Head Blight, Fusarium graminearum. Although the molecular details remain enigmatic, previous studies have suggested that C. rosea may secrete F. graminearum growth inhibitors. Further toward this, experiments described herein show that induction of C. rosea cultures by the addition of an aliquot of F. graminearum(Fg)-spent media (including macroconidia), yield C. rosea (Cr)-spent media that elicited higher anti-F. graminearum activity than either control or deoxynivalenol (DON)-induced Cr-spent media. To gain additional insight into the genetic and metabolic factors modulating this interaction, transcriptomic (RNAseq) profiles of C. rosea in response to DON and Fg-spent media treatment, were developed. This analysis revealed 24,112 C. rosea unigenes, of which 5,605 and 6,285 were differentially regulated by DON and F-spent media, respectively. More than half of these unigenes were up-regulated, with annotations, most notably in the Fg-spent media treatment data, suggesting enhancement of polyketide (PK) and non-ribosomal peptide (NRP) secondary metabolite precursor synthesis, and PK/NRP-like synthases. Four ABC transporters were also up-regulated in response to Fg-spent media. Further analysis showed that the PK and NRP-like synthases belong to three gene clusters that also include ABC transporters, and other genes known to tailor secondary metabolite biosynthesis. The RNAseq data was further validated using quantitative RT-qPCR. Taken together, these results show that C. rosea responds to the presence of Fg-spent media (and to a lesser extent, DON-alone) by up-regulating unique aspects of its secondary metabolism-related genetic repertoire. The identities and roles of C. rosea secondary metabolites produced by the targeted gene clusters are now under investigation.